Relationship between Mallampati Score and Success Rate of LMA Insertion at Ibnu Sina Hospital - Alfima, Mega; Dwimartyono, Fendy; Maharani, Ratih; Harahap, Wirawan; Dirgahayu, Andi Millaty Halifah (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: The most important action in successful resuscitation is to immediately open the respiratory tract. Airway management in surgical patients with general anesthesia can use tools, one of which is the Laryngeal Mask Airway. To anticipate LMA insertion failure, it is best to use a difficult intubation evaluation or what is known as the Mallampati Score. Objective: to determine the relationship between the Mallampati Score and the success of LMA insertion. Method: This research uses a quantitative analytical research design using a cross-sectional study approach with non-probability sampling technique. This research was conducted at Ibnu Sina Hospital in September-November 2023. Data analysis used univariate and bivariate analysis tests using cross-sectional tests. Results: The majority of respondents had a prediction of difficult intubation, namely 23 respondents (76.7%) while those who had a prediction of easy intubation were 7 respondents (23.3%) and 30 respondents (100%) had successful LMA insertion. There was no significant relationship between the Mallampati score and the success rate of LMA I-Gel insertion in patients at Ibnu Sina Hospital with a p-value of 0.397. Conclusion: The Mallampati score has no relationship with the success rate of LMA insertion.